Captura de enxames de abelhas africanizadas em área urbana no município de Botucatu, São Paulo, Brasil - Orsi, Ricardo de Oliveira [UNESP]; Contin Neto, Armando [UNESP]; Chan, Renie Venn [UNESP]; Garcia, Alex [UNESP]; Zaluski, Rodrigo [UNESP]; Kadri, Samir Moura [UNESP]; Souza, Edison Antonio de [UNESP]; Martins, Adriano [UNESP]; Silva, Rodrigo Lais da; Silva, Valdinei Moraes Campanucci da; Silva, Grazielle Venturelli Santos (Universidade Estadual Paulista (Unesp), 2015)
The increasing Africanized honeybees migratory swarms into urban areas it is related to the increase of accidents caused by these insects, due to its high defense behavior. The expansion of cities with large numbers of shelters and different blossoms during all year promotes the installation of bee colonies in these areas. Due to the importance of bees in beekeeping production and pollination areas of native vegetation and agricultural crops, it is important to establish prevent measures to accidents in urban areas and to provide correct destination for colonies. To quantify the incidence and collect colonies of Africanized honeybees in Botucatu, São Paulo, was established a partnership between the Beekeeping Area from College of Veterinary Medicine and Animal Science - FMVZ - UNESP and Botucatu Environmental Surveillance Health, Botucatu, São Paulo. The study was done between January 2013 and July 2015, and the requests to remove colonies were noted, inspected, followed by collection of colonies. 1371 occurrences were recorded, with 503 in 2013, 608 in 2014 and 260 by July 2015. The swarms were collected mainly in buildings (roofs, chimneys, walls, sewer manholes, water meter boxes and energy meters boxes), trees, poles, furniture, wooden boxes and cardboard, among others. 346 clusters (25.23%) of the occurrences were collected. Swarms collected were used for educational, research, extension and production proposes at the University. Considering the constant occurrence of colonies in urban areas, it is essential to maintain this work in order to prevent accidents and give proper destination the colonies.

A crescente migração de enxames de abelhas africanizadas para áreas urbanas vem aumentando os riscos de acidentes provocados por esses insetos, devido ao seu elevado instinto de defesa. A expansão das cidades que apresentam grande número de abrigos e sua arborização com espécies florais favorece a instalação de colônias de abelhas nessas áreas. Devido à importância das abelhas na produção apícola e na polinização de áreas de vegetação nativa e cultivos agrícolas, torna-se importante estabelecer medidas que evitem acidentes em áreas urbanas e para dar correta destinação aos enxames. Com objetivo de quantificar a incidência e realizar a coleta de enxames de abelhas africanizadas na cidade de Botucatu, São Paulo, estabeleceu-se uma parceria entre a Área de Apicultura da Faculdade de Medicina Veterinária e Zootecnia – FMVZ – UNESP e a Vigilância Ambiental em Saúde de Botucatu, São Paulo. O trabalho foi realizado entre Janeiro de 2013 e Julho de 2015, sendo as solicitações para retirada de enxames recebidas, anotadas, inspecionadas, seguida da coleta dos enxames. Foram registradas 1371 ocorrências, sendo 503 no ano de 2013, 608 em 2014, e 260 até julho de 2015. Os enxames foram coletados principalmente em construções (telhados, chaminés, muros, paredes, caixas de inspeção de esgoto, caixas de hidrômetros e de medidores de energia), árvores, postes, móveis abandonados, caixas de madeira e papelão, entre outros. Foram coletados 346 enxames (25,23%) das ocorrências. Os enxames coletados foram utilizados para fins de ensino, pesquisa, extensão e produção na Universidade. Considerando a constante ocorrência de enxames em áreas urbanas, torna-se indispensável a manutenção desse trabalho.
Keywords: Africanized honeybees; Urbanization; Accidents; Abelhas africanizadas; Urbanização; Acidentes